The Matter/Antimatter Issue - Dunning-Davies, Jeremy; Norman, Rich (European Journal of Applied Sciences, 2021)
From the moment it was first proposed, the Big Bang model has faced serious problems of one form and another. Amongst these was the fact that it proposed an initial balance between matter and antimatter but no collections of antimatter were observed. Here, this problem is addressed yet again, drawing on earlier work by several distinguished scientists but also advancing ideas based on recent analyses that have revealed a new seventh scalar part to the electromagnetic field with positive and negative energy.